Ano 'yon? ano 'yan? the whats and whys of being Filipino - Baron, Cynthia Sta. Maria; Yulo, Millet Yraola (Quezon City Baron Multimedia, 2008)
A dictionary of Filipino slang words and idioms.
In Filipino and English.
Fi-9097g donated by Dr. Ma. Teresa Sicat, Professor, Department of English & Comparative Literature, College of Art and Letters, UP Diliman.
Keywords: Filipino language -- Terms and phrases; Tagalog language -- Dictionaries -- English